Designing Interactive Video as an Innovative Teaching Media for Enhancing Speaking Skills: Embracing the 4Cs in Higher Education - Khairunnisa Br. Batubara; Christine Helena Natalia; Yuni Khairina (Universitas Negeri Medan, 2023)
In higher education, cultivating effective speaking skills is crucial for preparing students to succeed in today's dynamic and interconnected world. Traditional teaching methods often fall short of engaging students and promoting active learning. This research explores the potential of interactive video as an innovative teaching medium to enhance speaking skills while incorporating the 4Cs - Communication, Collaboration, Critical Thinking, and Creativity - into the learning process. The results indicate that interactive videos significantly impact students' speaking proficiency, as evidenced by improved pre-and post-assessment scores. Moreover, students reported enhanced engagement and motivation during the learning process, attributing it to the dynamic nature of interactive video content, which leverages multimedia elements, real-life scenarios, and interactive exercises. The results indicate that interactive videos significantly impact students' speaking proficiency, as evidenced by improved pre and post-assessment scores. Moreover, students reported enhanced engagement and motivation during the learning process, attributing it to the dynamic nature of interactive video content, which leverages multimedia elements, real-life scenarios, and interactive exercises. Furthermore, incorporating the 4Cs into interactive video design demonstrated transformative effects on students' speaking skills. Integrating collaborative activities fostered teamwork and communication among students, while critical thinking was stimulated through decision-making scenarios embedded within the videos. Additionally, the creative aspect of the interactive videos encouraged students to express their ideas and opinions more freely, ultimately boosting their confidence in public speaking. The findings of this research contribute to the growing body of knowledge on innovative teaching practices and the role of technology in higher education.